Dinâmica e imuno-histoquímica da vitelogênese durante processo de maturação ovariana no camarão Xiphopenaeus kroyeri (Heller, 1862) - Siebert, Tiago Henrique Rodrigues [UNESP] (2015)
The shrimp Xiphopenaeus kroyeri is among the most important shellfish species off the Brazilian coast, with several highlights such as social, economic, environmental and cultural. In addition, we highlight the wide geographic distribution in the western Atlantic coast (Rio Grande do Sul - BR to North Carolina - USA) and also the increase in artisanal fisheries with consequent reduction of the natural stocks. The lack of knowledge about the biology of the species, especially those targeted by fishing fleets, decreases the efficiency of strategies for protection of natural stocks. Knowledge about reproductive dynamics of a species is considered important and effective to control an exploited population. Regarding the crustaceans, the reproductive cycle is composed of ovaries at different stages of maturation, and the determination of these stages involves activities related to the ovary and hepatopancreas. These two organs work synchronously during vitellogenesis. The objectives of this study were to reevaluate some points in females in different stages of ovarian maturation. Macroscopic and microscopic classification of ovarian maturation and the cellular profile of hepatopancreatic tubules were studied by histological and histochemical analyzes; the location of vitellogenin synthesis in ovary and hepatopancreas was studied by immunohistochemistry and the gonadosomatic (GSI) and hepatosomatic (IHS) indices were compared. Thus, X. kroyeri ovary features six maturity stages: immature, pre-mature, early maturation, advanced maturation, mature and spawned. The germ cells exhibit six phases of development: oogonia type I, oogonia type II, pre-vitellogenic oocytes, oocytes in early vitellogenesis, oocytes in advanced vitellogenesis and mature oocyte. The hepatopancreatic tubule is lined by a pseudostratified epithelium with five cell types, cell E (undifferentiated) cells F (fibrillar), cell R (resorptive), B cell (vesicular) and cell M ...